COCOA MARKETING ANALYSIS (Theobroma cacao L.) IN KALIGARANG, KELING DISTRICT, JEPARA REGENCY - Rossi Prabowo; Dewi Hastuti; Siti Umi Nur Magfiroh (Jurnal Hexagro, 2024)
The marketing channel is the flow of goods from the producer to the final consumer and in the process it gives rise to marketing costs and the difference between the price received by the producer and that paid by the final consumer or what is commonly called the marketing margin. This research aims to determine the total costs, revenues and income of farming. cocoa in Kaligarang, Keling District, Jepara Regency. Knowing the cocoa marketing channels in Kaligarang, Keling District, Jepara Regency and knowing the marketing margin, the share received by producers (farmer's share) and the efficiency of cocoa marketing in Kaligarang Village, Keling District, Jepara Regency. The method used in this research is a quantitative descriptive method. Sampling of respondents using the census method from one Cacao farmer group. The research results show that there are 2 (two) types of marketing channels, namely type 1 starting from the producer to the middleman and to the final consumer with a marketing margin of IDR 6,000 Farmer share is 76.92% and the efficiency value is 1.89%, while type 2 marketing starts from producers to collecting traders then to wholesalers and finally to final consumers with a marketing margin of IDR 9,000,- farmer's share value is 68.96% and efficiency value is 2.31%.